Immune function? A missing link in the gender disparity in preterm neonatal outcomes. (2nd November 2017) - O'Driscoll, David N.; Greene, Catherine M.; Molloy, Eleanor J.
ABSTRACT: Introduction : In neonatology, males exhibit a more severe disease course and poorer prognosis in many pathological states when compared to females. Perinatal brain injury, respiratory morbidity, and sepsis, among other complications, preferentially affect males. Preterm neonates (born <37 weeks gestation) display a particularly marked sexual disparity in pathology, especially at the borders of viability. The sex biases in preterm neonatal outcomes and underlying multifactorial mechanisms have been incompletely explored. Sex-specific clinical phenomena may be partially explained by intrinsic differences in immune function. The distinct immune system of preterm neonates renders this patient population vulnerable, and it is increasingly important to consider biological sex in disease processes and to strive for improved outcomes for both sexes. Areas covered : We discuss the cellular responses and molecular intermediates in immune function which are strongly dependent on sex-specific factors such as the genetic and hormonal milieu of premature birth and consider novel findings in a clinical context. Expert commentary : The role of immune function in the manifestation of sex-specific disease manifestations and outcomes in preterm neonates is a critical prognostic variable. Further mechanistic elucidation will yield valuable translational and clinical information of disease processes in preterm neonates which may be harnessed for modulation.